2010
DOI: 10.4097/kjae.2010.59.2.82
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effective dose of rocuronium for lightwand tracheal intubation after induction with alfentanil, propofol, and low concentrations of sevoflurane

Abstract: BackgroundThe aim of this study was to determine the clinical effective dose of rocuronium for tracheal intubation using a lightwand after induction with propofol, alfentanil, and a low concentration of sevoflurane.MethodsTwenty-eight adults scheduled to undergo elective surgery lasting less than one hour were enrolled in this study. All patients received alfentanil (10 µg/kg) and propofol (1.5 mg/kg) for the induction of anesthesia. Tracheal intubation using a lightwand was attempted 3 minutes after administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Park et al described the optimal doses of rocuronium in lightwand intubation for short surgical procedures or outpatient surgery. The 50% and 95% clinical effective doses of rocuronium were 0.2 mg/kg and 0.35 mg/kg, respectively, which were lower than those for direct laryngoscopy intubation because rapid return to spontaneous ventilation is needed for day-care surgery (19). Few studies have reported clinical factors affecting successful lightwand intubation (4).…”
Section: Discussionmentioning
confidence: 99%
“…Park et al described the optimal doses of rocuronium in lightwand intubation for short surgical procedures or outpatient surgery. The 50% and 95% clinical effective doses of rocuronium were 0.2 mg/kg and 0.35 mg/kg, respectively, which were lower than those for direct laryngoscopy intubation because rapid return to spontaneous ventilation is needed for day-care surgery (19). Few studies have reported clinical factors affecting successful lightwand intubation (4).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to have a lowest optimal dose of 0.2 mg/kg, which provides good intubating conditions within three minutes, and a return of the first twitch on a train-of-four (TOF) at 15 minutes with a full TOF by 30 minutes. 4,5,6 Topicalising the airway The use of lignocaine, sprayed onto the vocal cords, aids intubation, but may not prevent the coughing experienced once the tube enters the trachea. Patients are often uncomfortable, with a resultant hoarse voice that may persist for a few hours.…”
Section: Using Small Doses Of Muscle Relaxantsmentioning
confidence: 99%